(untitled) (Brazilian Journal of Health Research, 2023)
Introduction: Considering the panorama of the pandemic and the experience in the management of complicated pregnancies resulting from infections with other coronaviruses, the vulnerability of pregnant women to SARS-CoV-2 was considered. Objectives: Analyze the scientific evidence and describe the main maternal and fetal complications associated with covid-19 during pregnancy. Methods: This is an integrative literature review, adapted following the Prisma method. Data collection took place through the following databases: National Library of Medicine National Institutes of Health (PubMed) and Science Direct. The descriptors and keywords were: “COVID-19”; “Pregnancy Complications Infectious”; “Mortality”; “Infectious Disease Transmission Vertical”. Results: Fifteen studies were included in this review, showing that pregnant women with covid-19 in a serious condition may have complications such as the need for Intensive Care Unit (ICU) (40%), pneumonia (33.4%), maternal death (33.4%) and preeclampsia. (20%). Among the fetal and neonatal complications, 60% corresponded to premature birth. In addition, the possibility of vertical transmission was reported. Conclusion: It is known that there are correlations of viral infections with repercussions and damage to maternal and fetal health. However, the specific complications of covid-19 and its severity in pregnant women, vertical transmission, perinatal and neonatal complications, are not completely understood. However, it a possible explanation for the difficulty in establishing a causal relationship is the symptoms of pregnancy.